Hydroxyapatite modified sludge-based biochar for the adsorption of Cu2+ and Cd2+: Adsorption behavior and mechanisms. (February 2021) - Chen, Yaoning; Li, Meiling; Li, Yuanping; Liu, Yihuan; Chen, Yanrong; Li, Hui; Li, Linshenzhang; Xu, Fangting; Jiang, Hongjuan; Chen, Li
Graphical abstract: Highlights: A new adsorbent (HAP-SSBC) was prepared from sludge and modified by hydroxyapatite. HAP-SSBC exhibited good adsorption affinity for Cu 2+ and Cd 2+ . The liquid film diffusion was the speed-limiting step. Main removal mechanisms are cation exchange, complexation and metal-π interaction. Abstract: This study prepared sewage sludge, a municipal solid waste, into a biochar modified by hydroxyapatite (HAP) as a new and efficient absorbent (HAP-SSBC) for removal of Cu 2+ and Cd 2+ from aqueous solution. Adsorption experiment revealed that HAP-SSBC exhibited significantly higher adsorption performance than raw sludge-based biochar (SSBC). At 298.15 K, the maximum adsorption capacity of Cu 2+ and Cd 2+ via Langmuir model were 89.98 and 114.68 mg/g, respectively. Adsorption kinetic experiment revealed that chemisorption was the main reaction. Analysis of X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy and X-ray photoelectron spectrum (XPS) further confirmed that the main mechanisms were ion exchange with Ca 2+, complexion by –OH and –COOH, and forming Cu-π or Cd-π binding with aromatic CC on HAP-SSBC surface. Overall, combing HAP and SSBC to be a new adsorbent is beneficial to the resource utilization of sludge and shows a good prospect for heavy metal removal in aqueous solution.